Chemistry Made Easy: Teaching Students about the Link Between Marine Chemistry and Coral Reef Biodiversity. Issue 2 (18th September 2020) - Curran, Mary Carla; Robertson, Alison
Teaching students about chemistry can be fun. Here, students learn that chemistry is linked to all marine life and affects where they live, the community that they live in, and what eats them. Some chemicals made by organisms have negative effects on humans and marine life, and these toxins and venoms can bioaccumulate in fish and affect human consumers who rely on critical marine resources for food. After learning about the role of chemistry in this food web and how humans might be affected by contaminated seafood, students can brainstorm about ways to increase food safety whilst considering community needs in regions of the world that may have economic difficulties. This activity has modifications for the visually impaired.